Silibinin Induces G2/M Cell Cycle Arrest by Activating Drp1-Dependent Mitochondrial Fission in Cervical Cancer - You, Yanting; He, Qiuxing; Lu, Hanqi; Zhou, Xinghong; Chen, Liqian; Liu, Huaxi; Lu, Zibin; Liu, Dongyi; Liu, Yanyan; Zuo, Daming; Fu, Xiuqiong; Kwan, Hiuyee; et al. (Frontiers in Pharmacology, 2020)
Cervical cancer is the fourth leading cancer type and the second most common gynecological malignancy among women worldwide. Silibinin (SB), a chief bioactive natural polyphenolic flavonoid of Silybum marianum L., has been used clinically for its hepatocyte protective effects. It also has anticancer effects via the induction of apoptosis and cell cycle arrest. However, the effects of SB on cervical cancer cells through mitochondrial fission have not been studied. Here, we showed that SB markedly suppressed cervical cells proliferation by inducing G2/M cell cycle arrest via the activation of dynamin-related protein 1 (Drp1), which in turn mediated the mitochondrial fission dysfunction both in vitro and in vivo. SB decreased the ATP content, mitochondrial membrane potential and mtDNA copy number, as well as reduced the reactive oxygen species levels in cervical cells. Furthermore, SB induced excessive mitochondrial fragmentation and reduced tubule formation. Further study showed that knockdown of Drp1 abolished the SB-induced G2/M cell cycle arrest in cervical cancer cells by inhibiting the mitochondrial fission pathway. More importantly, SB inhibited Hela cell growth in vivo model. In conclusion, we are the first to demonstrate that SB induces cervical cancer cell G2/M cell cycle arrest by activating Drp1-dependent mitochondrial fission dysfunction. This study suggests the strategy of inducing Drp1-dependent mitochondrial fission for cervical cancer prevention and treatment.